Risk factors and outcome of neonatal jaundice in a tertiary hospital - Bedowra Zabeen (IMC Journal of Medical Science, 2010)
Neonatal jaundice is a common cause of newborn hospital admission. The risk factors, the characteristics and outcomes related to neonatal jaundice in Bangladesh has not been studied so far. This study addressed the outcomes, characteristics and risks of the jaundiced newborn admitted into hospital. The babies who had significant jaundice and required phototherapy and /or exchange transfusion were investigated. A detailed history of delivery with gestational age was noted and clinical examination of the admitted newborn was done. Birth weight was recorded. The investigations included complete blood count, ABO and Rh compatibility, serum bilirubin, glucose 6 phosphate dehydrogenase (G6PD), thyroid stimulating hormone (TSH) and ultrasonography (USG) of brain. The newborns were closely monitored for the prognosis. The requirement of individualized phototherapy and exchange transfusion were also noted. Finally, the outcomes were recorded. Overall, 60 (m v. f = 58.3 v. 41.7%) newborns were found who developed significant jaundice and were investigated. Of them, 35% had gestational age less than 32wks and only 32% had equal to or greater than 35wks. Regarding delivery, 83.3 % had the history of caesarean section. ABO- and Rh– incompatibilities were found in 13.3% and 3.3%, respectively. Septicemia was diagnosed among 26.7% though blood culture yielded growth only in 20%. Compared with the higher gestational age-group ( 35 wks) the lower group (<32 wks) showed significantly higher rate of septicemia (12.5 v. 68.8%, p<0.005). G6PD deficiency was found in only one (1.7%) case. Birth asphyxia was found as a concomitant factor in three patients. Exchange transfusion was done only in 2 (3.3%) babies. Among them one was preterm IDM with septicemia and other had G6PD deficiency. None of these babies developed kernicterus. Five (8.3%) babies died, all of them had septicemia and one baby also had intraventricular hemorrhage (IVH) with PDA. The study revealed that a substantial number of neonatal jaundice had the history of lower gestational age in Bangladeshi newborns; and the lower gestational age is significantly associated with septicemia and possibly with hyperbilirubinemia. More study is needed to establish the study findings.